Reformulation of ultra-processed products in Colombia after the introduction of public health regulations - Elisa M. Cadena; Irieleth Gallo; Victoria Eugenia Soto (BMC Medicine)
Abstract Background The surge in ultra-processed food (UPF) intake and its association with the upsurge in non-communicable diseases in Colombia have motivated the implementation of multifaceted strategies to enhance the food landscape. These interventions include maximum sodium content in UPF, the introduction of front-of-package warning labeling (FOPL), and the implementation of taxes on sugar-sweetened beverages and UPF with excess sodium, sugars, and/or saturated fat content. These measures can effectively incentivize the reformulation of UPF, an area where empirical evidence remains limited within the country. Thus, this study aims to describe the changes in the content of nutrients between 2015 and 2024, when strategies promoting the reformulation of UPF were implemented. Methods This study is a quantitative observational repeated cross-sectional that analyzes the shifts in the nutritional profiles of UPF marketed in Colombia from 2015 to 2024. The researchers collected 200 matched product samples, comparing data from the 2015 National Nutrition Survey and in-store surveys conducted in Bogotá in 2024. The median values for energy and key nutrients, including sodium, sugars, saturated fats, calcium, zinc, iron, and vitamin A, were compared. Additionally, the team evaluated the use of FOPL based on established thresholds. Results The study revealed substantial decreases in the levels of sugars and sodium in UPF. The median sugar content in beverages plummeted from 8.9 to 4.8 g per 100 ml, whereas median sodium content in food products decreased from 400 to 296 mg per 100 g. Energy counts also saw significant decreases in beverages and processed meats. However, changes in saturated fat content were minimal, and certain subcategories, such as carbonated drinks, even presented increases in sodium. Regarding other micronutrients, an increase in calcium was observed in baked goods, but no consistent patterns emerged for the remaining vitamins and minerals. Conclusions Regulatory actions in Colombia appear to have changed the food landscape, fostering reformulation of UPF that drastically curtail the levels of detrimental nutrients such as sugars and sodium. Forthcoming studies should explore the dietary and health implications of these product changes, in addition to scrutinizing shifts in the use of additives and other ingredients. Trial registration Not applicable.